Ancient seed for modern cure - pomegranate review of therapeutic applications in periodontics - Arthiie Thangavelu; Sugumari Elavarasu; Rajasekar Sundaram; Tamilselvan Kumar; Dhivya Rajendran; Fairlin Prem (Wolters Kluwer Medknow Publications, 2017)
Punica granatum (pomegranate), the member of Punicaceae family, is used in the prevention and treatment of health disorders. P. granatum contains diverse range of phytochemicals including ellagic acid, punicalagin, pedunculagin, quercetin, rutin, tannic acid, polyphenol, anthocyanins, and catechins. This review aims at providing an overview of the chemical constituents, antibacterial, anti-inflammatory, and antioxidant properties of P. granatum, and its role in the prevention and treatment of gingival and periodontal diseases.